The international expansion of Singapore SMEs : exploring the extent to which ICT is likely to have an impact on the international expansion of Singapore SMEs. - Kwa, Hwee Ling. (2008)
Research on the effects that Information and Communications Technologies have on Small and Medium Enterprises and their chosen mode of entry. The primary objective of this research is to find out the extent to which ICT is likely to have an impact on the international expansion of Singapore SMEs.